The principle of minimum differentiation revisited: Return of the median voter - Nobuyuki Hanaki; Emily Tanimura; Nicolaas J. Vriend (Queen Mary University of London, School of Economics and Finance, 2016)
We study a linear location model (Hotelling, 1929) in which n (with n ≥ 2) boundedly rational players follow (noisy) myopic best-reply behavior. We show through numerical and mathematical analysis that such players spend almost all the time clustered together near the center, re-establishing the "Principle of Minimum Differentiation" that had been discredited by equilibrium analyses. Thus, our analysis of the best-response dynamics shows that when considering market dynamics as well as their policy and welfare implications, it may be important to look beyond equilibrium analyses.
Keywords: C72; D72; L13; R30; 330; Hotelling location model; Principle of Minimum Differentiation; Nash equilibrium; Best-response dynamics; Stochastic stability; Invariant measures